Vineland Sosyal-Duygusal Erken Çocukluk Ölçeği’nin (VSDEÇÖ) Türkçe Uyarlaması: Geçerlik ve Güvenirlik Çalışması / Turkish Adaptation of the Early Childhood Scale: The Validity and Reliability Study - Ceylan, Şehnaz; Kahraman, Özlem Gözün; Kılınç, Nida; Ülker, Pelin (Journal of History Culture and Art Research, 2019)
Vineland Social-Emotional Early Childhood Scales -SEEC The Vineland Social-Emotional Early Childhood Scales -SEEC was developed in 1998 by Sara S. Sparrow, David A. Balla and Domenic V. Cicchetti. Vineland SEEC aims to evaluate the social-emotional development of children from birth to 5 years and 11 months. The aim of this study is to adapt the Vineland Social-Emotional Early Childhood Scale to the Turkish culture in the 0-4 age group. The research was carried out with the data obtained from the parents who were between 0-4 years of age in 2017-2018. The study group of the study population of 102 (0.0-0.11 months), 126 (1.0-1.11) months 172 (2.0-2.11), 129 (3.0-3.11), 155 (4.0 4.11) age group, totally 684 children and those who undertake care. SPSS 22 package program and Lisrel package programs were used in the study. Data collected through Vineland Social-Emotional Early Childhood Scale and Personal Information Form were analyzed through SPSS and Lisrel package programs. Language validity, scope validity, construct validity, AFA (exploratory factor analysis) and DFA (confirmatory factor analysis) were used for validity. The internal consistency coefficients of the Vineland Social-Emotional Early Childhood Scale (Cronbach's alpha value) are .78 in the Interpersonal Relationship Sub-scale and .88 in the Play and Leisure subscale in children from birth to one year. In the Interpersonal Relationship subscale, an .77 age for children is. In the Interpersonal Relationship subscale, it was .64 in the Interpersonal Relationship subscale and .64 in the Scale of Coping, and .83 in the Scale of Coping Skills. There were 62 sub-scales in the Interpersonal Relations subscale and .64, and the Coping Skills Scale in. The four-year-olds had .70 in the Interpersonal Relations subscale, .74 in the Play and Leisure subscales, and .80 in the Coping Skills Scale. With these studies, the validity and reliability of the scale for the usage of the scale in Turkish culture has been obtained and the scale has been introduced to be used for different studies that can be done with children.